Management of age at puberty in beef heifers to optimize efficiency of beef production - Day, Michael L.; Nogueira, Guilherme de Paula [UNESP] (Oxford University Press (OUP), 2013)
Age at puberty in beef heifers can influence economic efficiency of beef production through effects on both age at first calving (2 vs. 3+ years of age) and the time of conception of heifers in their initial breeding season. An overarching factor that influences age at puberty in heifers is nutritional management during both the preweaning period and between weaning and the breeding season. Age at puberty is heritable and selection for precocious puberty in populations such as the Nelore breed has the potential to substantially influence production efficiency. Highly effective hormonal technologies exist to aid in induction of puberty in well managed heifers. Age at first ovulation and pregnancy in heifers can be substantially influenced through implementation of nutritional and/or hormonal manipulation strategies. In the long term, combinations of genetic selection, nutritional strategies, and hormonal intervention when necessary will optimize efficiency of this aspect of beef production.